2018
DOI: 10.1007/s00408-018-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Transient Blockade of Endothelin-1 Mitigates Amiodarone-Induced Pulmonary Fibrosis

Abstract: This finding may explain why ERAs are not an effective treatment for human pulmonary fibrosis. Nevertheless, they may be useful as an adjunct to therapeutic regimens involving drugs that have fibrogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The parameters of inflammation examined at 2 to 4 weeks post-AM were the same as those used to evaluate BLM-induced pulmonary fibrosis, and the results were similar to those seen with that model. Pretreatment with HJP272 produced significant reductions in all of these variables compared to AM alone, while post-treatment was ineffective, providing additional support for the hypothesis that the course of injury and repair is programmed at a very early stage of the inflammatory process [26]. The temporal effects of HJP272 were again most evident by examining lung morphological changes, which showed a much more limited fibrotic reaction in the pretreatment group (Figure 6).…”
Section: Am-induced Pulmonary Fibrosismentioning
confidence: 67%
See 1 more Smart Citation
“…The parameters of inflammation examined at 2 to 4 weeks post-AM were the same as those used to evaluate BLM-induced pulmonary fibrosis, and the results were similar to those seen with that model. Pretreatment with HJP272 produced significant reductions in all of these variables compared to AM alone, while post-treatment was ineffective, providing additional support for the hypothesis that the course of injury and repair is programmed at a very early stage of the inflammatory process [26]. The temporal effects of HJP272 were again most evident by examining lung morphological changes, which showed a much more limited fibrotic reaction in the pretreatment group (Figure 6).…”
Section: Am-induced Pulmonary Fibrosismentioning
confidence: 67%
“…As with the BLM model, HJP272 was administered intraperitoneally 1 h before treatment with AM or 24 h afterward [26]. The parameters of inflammation examined at 2 to 4 weeks post-AM were the same as those used to evaluate BLM-induced pulmonary fibrosis, and the results were similar to those seen with that model.…”
Section: Am-induced Pulmonary Fibrosismentioning
confidence: 80%
“…Amiodarone (AD) is an effective antiarrhythmic drug that has been linked to lung damage and can lead to fatal pulmonary fibrosis (PF) [1]. ADinduced lung injury may result from direct toxicity to lung tissues, hypersensitivity to AD, increased oxidative stress, changes in membrane properties, activation of alveolar macrophages, and cytokine release [2]. Several studies investigating the mechanism of AD-induced PF have been reported.…”
Section: Introductionmentioning
confidence: 99%